A Review Article on Exercise Intolerance in Long COVID: Unmasking the Causes and Optimizing Treatment Strategies - Koleničová, Veronika; Vňuková, Martina Sebalo; Anders, Martin; Fišerová, Marta; Raboch, Jiří; Ptáček, Radek (Medical science monitor, 2023)
There is a growing body of research on SARS-CoV-2 (PASC), previously known as the post-COVID syndrome, a chronic condition characterized by symptoms that persist after SARS-CoV-2 infection. Among these symptoms, feelings of physical exhaustion and prolonged fatigue are particularly prevalent and can significantly impact patients' quality of life. These symptoms are associated with reduced overall physical capacity, decreased daily physical activity, malaise after intense training, and intolerance to physical activity (IFA). IFA, described as a reduced ability to perform physical activities typical for the patient's age, can often lead to a sedentary lifestyle. Prolonged physical inactivity can cause deterioration in the overall physical condition and disrupt mitochondrial function, triggering a vicious cycle of gradual symptom worsening. The underlying causes of PASC remain unclear; however, several biochemical mechanisms have been discussed to explain the body's energy depletion, and a multidisciplinary approach that combines physical and cognitive rehabilitation and lifestyle interventions such as exercise and diet modifications has been suggested to improve the overall health and well-being of PASC patients. This critical review aims to review the existing research on the possible causes and links among chronic fatigue, reduced physical activity, and exercise intolerance in patients with PASC. Further research into the underlying causes and treatment of PASC and the importance of developing individualized treatment is needed to address each patient's unique health requirements.
Keywords: kvalita života; kognitivní trénink; lidé; Post-Acute COVID-19 Syndrome; Fatigue; SARS-CoV-2; postakutní syndrom COVID-19; Quality of Life; Cognitive Training; COVID-19; únava; Humans